Blood lactate accumulation during maximal cycling sprints and its relationship to sprint performance characteristics - Haase, R.; Dunst, A. K.; Nitzsche, N. (European Journal of Applied Physiology, 2025)
Purpose Blood lactate accumulation (Delta-BLC) during maximal short-term exercise is a crucial indicator of peak glycolytic activation in anaerobic performance assessment. However, the relationship between Delta-BLC and sprint performance remains inconsistent, potentially due to variations in testing protocols and the use of absolute rather than relative performance metrics. This study investigated the relationship between Delta-BLC and cycling sprint performance, hypothesizing normalization to body weight is essential for accurate metabolic performance evaluation.